Hemp fibre reinforced composites - Schwarzova, Ivana; Stevulova, Nadezda; Melichar, Tomas (International Conference “Environmental Engineering”, 2017)
The conventional homogeneous materials can no longer effectively satisfy the growing demands on product capabilities and performance, due to the advancement in products design and materials engineering. Therefore, the fibre reinforced composites with better properties and desirable applications emerged. Natural fibres have high strength to low weight ratios and have good sound and thermal insulation properties. Combination of organic filler and inorganic matrix creates high-quality products such as fibre boards and composites. The great importance is attached to industrial hemp as source of the rapidly renewable fibres and as non-waste material. Industrial hemp fibre has great potential in composite materials reinforcement. However, improving interfacial bonding between fibres and matrix is an important factor for its using in composites. This paper deals with hemp fibre reinforced composites in civil engineering as component part of sustainable construction. Prepared lightweight composites based on original and pre-treated hemp hurds are characterized by selected physical and mechanical properties (density, thermal conductivity, water absorbability, compressive and tensile strength) in dependence on used inorganic binder (traditional Portland cement and alternative MgO-cement).